2012
DOI: 10.5830/cvja-2012-022
|View full text |Cite
|
Sign up to set email alerts
|

An audit of pregnant women with prosthetic heart valves at a tertiary hospital in South Africa

Abstract: BackgroundCardiac disease in pregnancy is a common problem in under-resourced countries and a significant cause of maternal morbidity and mortality. A large proportion of patients with cardiac disease have prosthetic mechanical heart valve replacements, warranting prophylactic anticoagulation.AimTo evaluate obstetric outcomes in women with prosthetic heart valves in an under-resourced country.MethodsA retrospective chart review was performed of 61 pregnant patients with prosthetic valve prostheses referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 27 publications
(48 reference statements)
2
60
0
3
Order By: Relevance
“…27 There were seven retrospective studies, two population-based cohort studies, 20,21 two multicentre unselected case series 28,32,33 and three single-centre unselected case series 28,30,31 (Table 1). Ten studies captured a total of 305 women undertaking 392 pregnancies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27 There were seven retrospective studies, two population-based cohort studies, 20,21 two multicentre unselected case series 28,32,33 and three single-centre unselected case series 28,30,31 (Table 1). Ten studies captured a total of 305 women undertaking 392 pregnancies.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies reported information on maternal mortality and any pregnancy loss. Eight of the 11 studies allowed identification of perinatal mortality 20,21,[27][28][29]31,32,34 and three studies had insufficient details to differentiate early pregnancy loss from fetal death at >22 weeks. 30,33,35 No studies reported the incidence of infective endocarditis or neonatal admissions to the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Częstość występowania IZW u kobiet w ciąży ocenia się na 0,006% [196]. Częstość IZW u kobiet z chorobą serca wynosi 0-1,2% i jest wyższa u kobiet z mechaniczną protezą zastawkową [461][462][463][464]. Dlatego też IZW u kobiet w ciąży spotyka się wyjątkowo rzadko, a choroba może wynikać z wcześniej istniejącego uszkodzenia serca lub uzależnienia od dożylnych narkotyków.…”
Section: Infekcyjne Zapalenie Wsierdziaunclassified
“…[15] Warfarin is therefore not recommended in the first trimester (grade 1A). [16][17] In addition, there is an increased risk of fetal ocular and neurological abnormalities, a 30% risk of fetal loss, and an increased risk of fetal intracranial haemorrhage at any time during pregnancy, but particularly at the time of delivery. [3,[18][19][20][21] In pregnant women at higher risk of thromboembolism, such as those with older-generation valve types in the mitral position, e.g.…”
Section: Warfarinmentioning
confidence: 99%